Factors Affecting Implementation of the Balanced Score Card Studi Empiris pada PT. Bank Tabungan Negara (Persero), Tbk. - Amilia Paramita Sari (LPPM Universitas Adiwangsa Jambi, 2024)
The aim of this study is to find the relationship between corporate culture and the implementation of the Balanced Scorecard (BSC) through empirical studies, through the execution of 115 questionnaires at the PT. Bank Tabungan Negara (Persero), Tbk., and using factor analysis and logistical regression analysis based on the model of O'Reilly et al. and Denison. The results of this research show that corporate cultural factors have a significant positive influence on the implementation of BSC. The research results show that data analysis of innovation, result orientation, team orientation, and stability have significant relationships with BSC implementation. The results also showed that there was no correlation between attention to detail and BSC implementation.